Supporting Acquisition of Spelling Skills in Different Orthographies Using an Empirically Validated Digital Learning Environment - Juhani Lyytinen, Heikki; Semrud-Clikeman, Margaret; Li, Hong; Pugh, Kenneth; Richardson, Ulla (Frontiers in Psychology, 2021)
This paper discusses how the association learning principle works for supporting acquisition of basic spelling and reading skills using digital game-based learning environment with the Finland-based GraphoLearn (GL) technology. This program has been designed and validated to work with early readers of different alphabetic writing systems using repetition and reinforcing connections between spoken and written units. Initially GL was developed and found effective in training children at risk of reading disorders in Finland. Today GL training has been shown to support learning decoding skills among children independent of whether they face difficulties resulting from educational, social or biological reasons.